2011
DOI: 10.1590/s1984-82502011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approaches for tumor necrosis factor inhibition

Abstract: Tumor necrosis factor (TNF) consists of an inflammatory cytokine essential for homeostasis and organism defense. Despite its physiological relevance, both increased biosynthesis and release of TNF lead to the exacerbation of inflammatory and oxidative responses, which are related to the pathogenesis of a host of diseases of an inflammatory, autoimmune and/or infectious nature. In this context, effective therapeutic approaches for the modulation of TNF have been the focus of research efforts. Approximately one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…The TNFRSF1a is an established receptor for soluble TNFα, and it has also been reported that mutation in TNFRSF1a decreases TNFα-induced apoptosis. 32 38 39 TNFα is regulated by the transcription factor, NF-kB, 40 and we observed that loss of MLK3 was able to induce NF-kB in CD4 + T cells, and therefore, we can speculate that induction of NF-kB can increase TNFα production due to loss of MLK3. We also observed that loss of MLK3 induced CD70 expression on T cells, and it is reported that treatment of human peripheral blood mononuclear cells with CD70 induces rapid decrease of inhibitor of kappa B (IκBα), indicating that CD70-CD27 axis can trigger activation of the canonical NF-kB pathway and this could result in TNFα induction/synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…The TNFRSF1a is an established receptor for soluble TNFα, and it has also been reported that mutation in TNFRSF1a decreases TNFα-induced apoptosis. 32 38 39 TNFα is regulated by the transcription factor, NF-kB, 40 and we observed that loss of MLK3 was able to induce NF-kB in CD4 + T cells, and therefore, we can speculate that induction of NF-kB can increase TNFα production due to loss of MLK3. We also observed that loss of MLK3 induced CD70 expression on T cells, and it is reported that treatment of human peripheral blood mononuclear cells with CD70 induces rapid decrease of inhibitor of kappa B (IκBα), indicating that CD70-CD27 axis can trigger activation of the canonical NF-kB pathway and this could result in TNFα induction/synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…An alternative to TNF-a hyper-response modulation in COVID-19 infections is the use of anti-TNF-a antibodies (75). However, most drugs that target TNF-a also block bioavailable TNF-a that monocytes and T cells produce, increasing the susceptibility to viral or bacterial coinfection or reinfection (76). AM3 normalizes the TNF-a production (27); in particular, AM3 inhibited TNF-a production by 90% compared to sera from placebo-treated mice.…”
Section: Am3 and Cytokinesmentioning
confidence: 99%
“…They resulted in higher and constitutive TNF-α expression and were associated with an increased risk of HCC [ 10 , 17 ]. TNF-α itself is a potent pro-inflammatory cytokine [ 17 , 59 ]. Necroinflammation in hepatocytes triggers mutagenesis and activation of oncogenes from proto-oncogenes in host cells, causing HCC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%